Orthodox Communities and Partisan Movement in Kuzbass in 1919 - A. V. Gorbatov (Tsentr nauchnykh i obrazovatelnykh proektov, 2021)
The results of the analysis of the tragic stage in the history of the Russian Orthodox Church during the civil war in the Kemerovo region are presented. Based on materials from periodicals and archives, as well as on the research of secular and church historians, the partisan pogroms of 1919 are considered as events that had a negative impact on the life of the church as a social institution. It is noted that pogroms and murders of believers and clergy took place everywhere in the territory of Kuzbass. It was revealed on the basis of documentary evidence that the main target of the attack of the red partisans was the clergy. Punitive operations continued throughout 1919, but the peak of the pogroms is associated with the activities of the united detachment under the command of G. F. Rogov and I. P. Novoselov in December in the Kuznetsk district. It is shown that the Russian Orthodox Church was seized by an institutional crisis, the parish life of the counties was upset, the number of clergy decreased, and some of the clergy left the region.